Correlational study of the prevalence of burnout in student-athletes and the quality of sleep - Ang, Han Teng (2019)
This study aims to investigate the correlation between the prevalence of burnout and sleep quality in student-athletes in Singapore. All the participants went through a three-section questionnaire through an online survey platform. The questionnaires that were used in this study was the Athlete Burnout Questionnaire (ABQ) to test for the prevalence of burnout, and the Pittsburgh Sleep Quality Assessment (PSQI). A significant correlation was not found when physical and emotional exhaustion was tested with the quality of sleep. A significant correlation was also not found when reduced sense of accomplishments was tested with the quality of sleep. A significant correlation was not found when the global burnout average and sport devaluation were tested with the quality of sleep. This study aims to provide information to institutions in better understanding their student-athletes, in terms of the prevalence of burnout and their quality of sleep, and possibly help the students by altering their curriculum.